Reducing the Agricultural Gender Gap in Cote d'Ivoire : How has it Changed? - Donald, Aletheia; Lawin, Gabriel; Rouanet, Lea (World Bank, Washington, DC, 2020)
Over the last decade, Cote d’Ivoire has witnessed a remarkable shrinking of its gender gap in agricultural productivity. When comparing similar households, the gender gap has been reduced by 32 percent.